"Who'll do all these if I'm not around?": Bonding social capital and health and well-being of inpatients. Issue 1 (1st January 2018) - Amoah, Padmore Adusei; Koduah, Adwoa Owusuaa; Gyasi, Razak Mohammed
ABSTRACT: Purpose : Although social capital influences health-related decisions and behavioural patterns in many developing countries, minimal attention has been paid to the nuances of its effect on healthcare. This paper examines how bonding social capital affects healthcare delivery for inpatients in Ghana. Methods : Semi-structured in-depth interviews were used and thematic analysis method employed to analyse the data. Interviews were conducted with health professionals and relatives and close friends of inpatients in three public health facilities in Ashanti region. Results : Relatives and close friends of inpatients were a critical source of instrumental support such as provision of meals, laundry services, running errands and financial assistance as well as emotional support. These functions—that were both 'expected' and 'encouraged'— reduced the burden on the health facilities, which apparently had limited resources to offer adequate care. However, the relatives of inpatients sometimes inadvertently obstructed efficient healthcare delivery through actions such as extending 'unapproved' alternative care to patients. Moreover, the process of contributing towards health and well-being of the sick exposed the relatives to health risks due to poor living conditions. Conclusion : A well-defined and befitting role must be devised for at least an immediate social relation of inpatients to improve the positive effects of bonding social capital on healthcare delivery.